TUTORIAL MENGGUNAKAN MEDIA FACEBOOK : MOTIVASI BERWIRAUSAHA : MEMULAI USAHA DARI NOL - Kasman, Kasman; Wahyudi, Dedy; Hamdanur, Peris; Yusuf, Andi Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service activity aims to motivate partners to start micro businesses through tutorials using Facebook media that can reach more participants and can be re-learned according to the availability of time The method of implementation is to use Facebook media which has a wider reach to hold tutorials. Participants were very enthusiastic about the tutorial through Facebook media, as evidenced by the number of participants for one series of tutorials which were up to 300 percent above the target. With this tutorial, participants can repeatedly watch video tutorials so that they are more motivated to set up a micro business that starts from scratch. Mentoring activities are still needed so that simple financial reports compiled by the participants can be more motivated to establish micro businesses.